2014
DOI: 10.1002/app.40826
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of hierarchical composites enhanced by pristine graphene and graphene oxide nanoinclusions

Abstract: Epoxy resin nanocomposites incorporated with 0.5, 1, 2, and 4 wt % pristine graphene and modified graphene oxide (GO) nanoflakes were produced and used to fabricate carbon fiber-reinforced and glass fiber-reinforced composite panels via vacuum-assisted resin transfer molding process. Mechanical and thermal properties of the composite panels-called hierarchical graphene composites-were determined according to ASTM standards. It was observed that the studied properties were improved consistently by increasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 30 publications
1
43
0
Order By: Relevance
“…Graphene nano platelets (GnPs) which has been recently developed single layered carbon nano material is a useful polymer reinforcement material which has a large surface area led to increase the stress transfer between polymer and nano material [4,5,6,7]. Graphene has a 2-D nanostructure and leads an enhancement in toughness of fibers [8,9]. Several researchers reported that the graphene nano material addition in the fiber reinforced composites significantly affects the mechanical [10,11], dynamic [12], thermal [13] and electrical [14] properties materials.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene nano platelets (GnPs) which has been recently developed single layered carbon nano material is a useful polymer reinforcement material which has a large surface area led to increase the stress transfer between polymer and nano material [4,5,6,7]. Graphene has a 2-D nanostructure and leads an enhancement in toughness of fibers [8,9]. Several researchers reported that the graphene nano material addition in the fiber reinforced composites significantly affects the mechanical [10,11], dynamic [12], thermal [13] and electrical [14] properties materials.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of poisson's effect also plays an important role [23]. The resistivity and changes in dimension may be related to the fiber buckling, delamination, cracks, voids, internal defects and secondary phase of the composites [26][27][28][29][30]. However, the relation between dimensional changes and resistivity changes because of the loading and unloading requires more research.…”
Section: Figurementioning
confidence: 99%
“…During service, honeycomb-structured polymeric composites are subjected to a wide range of mechanical loads and environmental conditions, such as high and low temperatures, moisture, hydraulic fluids, and other solvents [20][21][22][23][24][25][26][27]. When compared to other structural materials, polymeric materials can absorb more water, hydraulic fluids, and solvents from internal and external sources into their structures.…”
Section: Compression Tests On Honeycomb Compositesmentioning
confidence: 99%